Effects of ditch‐buried straw return on water percolation, nitrogen leaching and crop yields in a rice–wheat rotation system. (24th April 2015) - Yang, Haishui; Xu, Mingmin; Koide, Roger T; Liu, Qian; Dai, Yajun; Liu, Ling; Bian, Xinmin
Abstract: BACKGROUND: Crop residue management and nitrogen loss are two important environmental problems in the rice–wheat rotation system in China. This study investigated the effects of burial of straw on water percolation, nitrogen loss by leaching, crop growth and yield. Greenhouse mesocosm experiments were conducted over the course of three simulated cropping seasons in a rice1–wheat–rice2 rotation. RESULTS: Greater amounts of straw resulted in more water percolation, irrespective of crop season. Burial at 20 and 35 cm significantly reduced, but burial at 50 cm increased nitrogen leaching. Straw at 500 kg ha −1 reduced, but at 1000 kg ha −1 and at 1500 kg ha −1 straw increased nitrogen leaching in three consecutive crop rotations. In addition, straw at 500 kg ha −1 buried at 35 cm significantly increased yield and its components for both crops. CONCLUSIONS: This study suggests that N losses via leaching from the rice–wheat rotation may be reduced by the burial of the appropriate amount of straw at the appropriate depth. Greater amounts of buried straw, however, may promote nitrogen leaching and negatively affect crop growth and yields. Complementary field experiments must be performed to make specific agronomic recommendations. © 2015 Society of Chemical Industry